Does Founders' Socioeconomic Status Matter for the Success of Start-ups? : Case of VSE graduates - Caraseni, Chirill; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This qualitative study investigates the influence of parental socio-economic status (SES) on the growth and performance of startups through in-depth interviews with founders from diverse backgrounds. The objectives were to understand founders' perspectives on how family social class, education, and parental occupation shaped startup success, identify mechanisms linking parental SES to entrepreneurial outcomes, and examine contextual factors like the entrepreneurial ecosystem. Findings revealed a nuanced interplay between parental SES, access to resources/networks, entrepreneurial mindsets, and risk-taking. Higher SES backgrounds provided advantages in financial capital, mentorship, and connections, while lower SES posed challenges. However, parental values, education, and occupations also shaped founders' perspectives beyond material resources.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses